Evaluation of a play-based curriculum in four Philippine private schools - Enverga, Elizabeth R. (2006)
This was an attempt of the study to evaluate the adaptability of the Play-based Curriculum in the Philippine setting and its effectiveness. Four schools were used as sample and classes of 4 to 5 year olds were observed by the researcher. The paper used comparison as its methodology. The findings of the study suggested that the 4 schools have common features in employing play-based curriculum in terms of the guideline/standards of play-based curriculum as set by the National Association for Educating Young Children (NAEYC). The play based curriculum assists in all aspects of children's development: physical, social, emotional, intellectual and moral. It was suggested that pre-schools should adopt a play-based curriculum.